Vibration analysis for failure detection in low pressure steam turbine blades in nuclear power plant. (February 2018) - Zhao, Wensheng; Li, Yanhui; Xue, Meixin; Wang, Pengfei; Jiang, Jin
Abstract: This paper presents an investigation of the failure of a low-pressure steam turbine blade in a pressurized water reactor (PWR) nuclear power plant. The dynamical behaviour of the blade is analyzed theoretically and experimentally. A three-dimensional finite element model is used to predict the blade resonances in the operational speed range. Natural frequencies and mode shapes of the blade at static condition are obtained, then natural frequencies of the blade at different rotational speeds are calculated with consideration of centrifugal force and steam flow forces. A Campbell diagram is plotted to predict the likely operational conditions that may cause resonant vibration of the blade. Vibration tests are conducted to determine the vibration characteristic of the blade. It is found that the 2nd natural frequency of the blade is very close to the 9th rotor speed harmonic. The experimental natural frequencies are in good agreement with the finite element predicted values. Fretting wear is observed at the concave root surfaces of the blade trailing edge caused by resonant vibration. The fracture surface of the cracked blade shows typical fatigue patterns. The fretting wear characteristics in the crack initiation regions are observed. Stress distribution of the blade at the 9th harmonic frequency is analyzed using an elastic-plastic finite element model. Fretting fatigue experiments indicate that the fatigue life of the blade is greatly reduced due to fretting wear. The results of the investigation show that the failure of the blade is attributed to a combination of high cycle fatigue (HCF) and fretting wear. Highlights: The blade failure is due to high cycle fatigue and fretting wear. The 2nd blade vibration mode is likely to be in resonance with the 9th harmonic. The blade fatigue life is greatly reduced due to fretting wear. Wear debris adhered to the surface causes the crack initiation and propagation. SEM fractography of fracture surface shows fretting fatigue characteristics.